Model Management of Innovative Development of Industrial Enterprises (Eurasian Research Bulletin, 2023)
The purpose of the study is to develop the theoretical and methodological provisions, as well as the practical recommendations for the management of the innovative development of the industrial enterprises of a vertically integrated structure, which is considered as one of the mechanisms to improve its competitiveness. The result of the study is the development of a structural and parametric model of the innovative enterprise management and the creation of a mechanism to improve the efficiency of its activities.